Innovation and Collaboration-Based Islamic Education Management Model in the Post-Digital Era - Hakimudin; Permata Sari, Putri; Mas Ayu, Sovia (Universitas Islam Negeri Raden Intan Lampung, 2025)
The transformation of Islamic education in the post-digital era demands a management model that is adaptive to technological and social dynamics. This research analyzes the management model based on innovation, collaboration, and sustainability in Madrasah Aliyah Negeri 1 Bandar Lampung through a qualitative case study. The results show that the main innovation is manifested in the integration of specific digital infrastructure, namely the Madrasa Digital Center (MDC), library automation system (SLiMS), and digitization of website-based learning tools. The dominant collaboration pattern adopts a pentahelix approach involving strategic synergies between madrasas, universities (UIN Raden Intan), government agencies (BRIN, MoRA), and the private sector. The scientific contribution of this research is the formulation of an integrated Islamic education management model that transforms sporadic digitization into a systematic learning ecosystem. The model provides an empirical framework for madrasas to sustainably improve digital literacy, graduate competitiveness and management effectiveness in the post-digital era.